Why They Are Different: Based on the Burden of Disease Research of WHO and Institute for Health Metrics and Evaluation. (23rd April 2018) - Yoon, Seok-Jun; Kim, Young-Eun; Kim, Eun-Jung
Abstract : Objectives . We traced the methodology of measuring the burden of disease of IHME and WHO in detail and we would like to present various perspectives on the aspects that can be acceptable in Korea or not. Study Design . We investigate the methodology and the major outcomes of the studies of burden of disease and show the direction of our future research. We studied and compared WHO's and IHME's outcomes in aspect of the data source, methodological differences, and the interpretation ways. Results . Despite the in-depth review, there was "black box" that could not be explained specifically. But there were some estimations and using of data from developed countries which had well-developed population polls. In addition, using DisMod-MR for metaregression of IHME was different from WHO's DisMod-2. Discussion . It will be necessary to secure the validity of the claim data in order to trace the accuracy of the disease diagnosis. At last, the accuracy of the data used to construct the disease burden survey system should be promoted. To this end, we propose to introduce a cause-of-death estimation system, linking the cause-of-death report and the health insurance claiming system with the electronic medical records that the hospital produces.